Modern software for the numerical study of flow in hydraulic machines - Krupa, Y. S.; Demchuk, Yevheniia (Національний технічний університет "Харківський політехнічний інститут", 2022)
In the past few decades, the field of developing computer software systems has been actively developing, which in turn leads to competition in the software market. Qualified engineers working in the hydroturbine industry must be able to use a computer not only at the user level, but also at the programmer level in order to program modules for their own needs based on existing software systems. Recently, numerical simulation has become applicable to an ever wider class of flows, replacing experimental research methods. Certain numerical models are characterized by different areas of applicability and expenditures of computational resources. The paper provides an analytical review of modern CFD software systems. The advantages and disadvantages of these programs are analyzed in terms of building a three-dimensional model of the object of study, creating a computational grid, setting boundary conditions and visualizing the calculation results. The analysis and comparison of existing mathematical models that used to calculate the spatial flow in the flow path of hydraulic machines has been carried out. There are many different programs for solving hydrodynamic problems, some of the advanced commercial software systems are Ansys, SolidWorks Flow Simulation, Autodesk CFD. There are also open source software products. These automatic design systems make it possible not only to perform high-quality modeling of systems of various physical nature, but also to study the response of these systems to external influences in the form of distributions of pressures, temperatures, and velocities. The calculation algorithms in the programs are similar; the distinctive features of the programs can be evaluated according to the following criteria: grid generation, accuracy, reliability (convergence), calculation speed, model physics, system flexibility. The use of modern software packages for studying the hydrodynamic characteristics of the flow in hydraulic machines significantly reduces the time and material resources in comparison with physical modeling.

В останні кілька десятиліть активно розвивається сфера розробки обчислювальних програмних комплексів, що у свою чергу призводить до конкуренції на ринку програмного забезпечення. Кваліфіковані інженери, що працюють в галузі гідротурбобудування повинні володіти комп'ютером не лише на рівні користувача, а й на рівні програміста, щоб на базі існуючих програмних комплексів програмувати модулі для власних потреб. Останнім часом чисельне моделювання стає застосовним до дедалі ширшого класу течій, замінюючи собою експериментальні методи дослідження. Ті чи інші чисельні моделі характеризуються різними областями застосування та витратами обчислювальних ресурсів. У роботі проведено аналітичний огляд сучасних програмних комплексів CFD. Проаналізовано переваги та недоліки даних програм у частині побудови тривимірної моделі об'єкта дослідження, створення розрахункової сітки, завдання граничних умов та візуалізації результатів розрахунку. Проведено аналіз та порівняння існуючих математичних моделей, що застосовуються для розрахунку просторової течії у проточних частинах гідромашин. Для вирішення гідродинамічних задач існує багато різних програм, одними з передових комерційних програмних комплексів є Ansys, SolidWorks Flow Simulation, Autodesk CFD. Так само існують програмні продукти з відкритим вихідним кодом. Дані системи автоматичного проектування дозволяють як виконати якісне моделювання систем різної фізичної природи, так і досліджувати відгук цих систем на зовнішні впливи, таких як: розподіл тисків, температур, швидкостей. Алгоритми проведення розрахунку у програмах схожі, відмінні риси програм можна оцінити за такими критеріями: генерація сітки, точність, надійність (збіжність), швидкість обчислень, фізика моделі, гнучкість системи. Використання сучасних пакетів програм для дослідження гідродинамічних характеристик потоку в гідромашинах значно зменшує витрати часу та матеріальних ресурсів, порівняно з фізичним моделюванням.
Сучасне програмне забезпечення для чисельного дослідження потоку в гідромашинах
Keywords: hydraulic machines; numerical research; hydrodynamic calculation; mathematical model; spatial flow; CAD systems; гідравлічні машини; чисельне дослідження; гідродинамічний розрахунок; математична модель; просторова течія; системи автоматичного проектування